Pengaruh Budaya Organisasi terhadap Efektivitas Manajemen Gereja - Lysda Hartaty Huwae; Beni Chandra Purba; Budi Kelana (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2023)
Abstract This research explores the influence of organizational culture on church management effectiveness, a crucial aspect in the dynamics of religious life within communities. Through a qualitative descriptive approach, we delve into various sources to gain a profound understanding of this phenomenon. Our findings highlight that the church's organizational culture comprises norms, values, and assumptions that shape its unique identity. Dimensions such as communication, training, recognition, decision-making, risk-taking, planning, collaboration, and management practices contribute to this organizational culture framework. Church management effectiveness, as an effort to integrate resources to achieve the church's goals, is influenced by various factors such as organizational characteristics, environment, members, and management practices. The close relationship between organizational culture and church management is key to achieving effectiveness, while weak culture can impede church goals. Furthermore, a positive organizational culture positively impacts church members' performance and creates an adequate religious environment. In conclusion, a strong relationship between organizational culture and church management supports the growth and sustainability of the church in fulfilling its mission and goals. Thus, a deep understanding of the dynamics of church organizational culture can help enhance church management effectiveness and contribute positively to the religious life of communities.